A general forcefield for accurate phonon properties of metal–organic frameworks. Issue 42 (12th October 2016) - Bristow, Jessica K.; Skelton, Jonathan M.; Svane, Katrine L.; Walsh, Aron; Gale, Julian D.
Abstract : We report the development of a forcefield capable of reproducing accurate lattice dynamics of metal–organic frameworks. Abstract : We report the development of a forcefield capable of reproducing accurate lattice dynamics of metal–organic frameworks. Phonon spectra, thermodynamic and mechanical properties, such as free energies, heat capacities and bulk moduli, are calculated using the quasi-harmonic approximation to account for anharmonic behaviour due to thermal expansion. Comparison to density functional theory calculations of properties such as Grüneisen parameters, bulk moduli and thermal expansion supports the accuracy of the derived forcefield model. Material properties are also reported in a full analysis of the lattice dynamics of an initial subset of structures including: MOF-5, IRMOF-10, UiO-66, UiO-67, NOTT-300, MIL-125, MOF-74 and MOF-650.